Performance improvement of a graphene patch antenna using metasurface for THz applications - Shubham A.; Samantaray D.; Ghosh S.K.; Dwivedi S.; Bhattacharyya S. (My University, 2025)
This paper presents the design and development of a miniaturized, efficient graphene-based reconfigurable antenna working in the terahertz (THz) domain. This design puts forward the analysis of a graphene-based microstrip patch antenna loaded with a graphene metasurface (MS) as a superstrate configuration. The MS is designed over a silicon dioxide (SiO2) substrate in which the square-shaped unit cells have been organized with a periodicity of λ/10.4, referred to as the lowest operating frequency. The proposed antenna operates over the lower THz frequency band of 1.44–2.84 THz; providing a bandwidth of 1.4 THz with a return loss dip of 35.54 dB at 2.02 THz. The maximally achieved realized gain and radiation efficiency at 2.74 THz are 8.91 dBi and 70.14%, respectively. The proposed antenna further exhibits the beam scanning feature over a range close to 50°. The proposed graphene-based MS structure is compact, directive, and highly efficient in the THz domain. It finds useful applications in biomedical, satellite communication, high-quality video imaging, etc. © 2022 Elsevier GmbH